2018
DOI: 10.1039/c7gc03029k
|View full text |Cite
|
Sign up to set email alerts
|

Biomass pretreatment using deep eutectic solvents from lignin derived phenols

Abstract: In future biorefineries, the development of inexpensive and renewable reagents for biomass pretreatment is highly desirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
158
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(161 citation statements)
references
References 28 publications
0
158
1
2
Order By: Relevance
“…Pioneering works have indicated that DES pretreatment can significantly promote the efficacy of residue cellulose enzymatic hydrolysis. The plant species, which on the pretreatment with different DESs, have been extended to gramineae [corncob (Procentese et al, 2015;Zhang et al, 2016), wheat straw (Jeong et al, 2015), sorghum (Das et al, 2018), and switchgrass (Chen et al, 2018;Kim et al, 2018)], hardwood [eucalyptus (Shen et al, 2019), willow (Lyu et al, 2018;Song et al, 2019), and poplar (Alvarez-Vasco et al, 2016;Liu et al, 2017)], softwood [pine (Lynam et al, 2017), spruce (Wahlström et al, 2016), and fir (Alvarez-Vasco et al, 2016)], and endocarp (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering works have indicated that DES pretreatment can significantly promote the efficacy of residue cellulose enzymatic hydrolysis. The plant species, which on the pretreatment with different DESs, have been extended to gramineae [corncob (Procentese et al, 2015;Zhang et al, 2016), wheat straw (Jeong et al, 2015), sorghum (Das et al, 2018), and switchgrass (Chen et al, 2018;Kim et al, 2018)], hardwood [eucalyptus (Shen et al, 2019), willow (Lyu et al, 2018;Song et al, 2019), and poplar (Alvarez-Vasco et al, 2016;Liu et al, 2017)], softwood [pine (Lynam et al, 2017), spruce (Wahlström et al, 2016), and fir (Alvarez-Vasco et al, 2016)], and endocarp (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Main substructures are depicted in Figure . The cross‐signals in the 2D HSQC spectra of the samples were assigned by comparison with the published literature . The quantitative analysis of the structure features of all the samples were conducted according to the method reported by a previous paper …”
Section: Resultsmentioning
confidence: 99%
“…Besides its conversion into MA, catechol obtained from engineered bioenergy crops could represent a value-added product since it is a starting material for the manufacturing of insecticides (e.g., carbofuran and propoxur), fragrances, drugs, and polymerization inhibitors [39]. Recently, catechol was converted to a deep eutectic solvent (DES) that was found to be effective for the pretreatment of plant biomass and facilitate the removal of lignin prior enzymatic saccharification [40].…”
Section: Muconic Acidmentioning
confidence: 99%
“…Other engineered microbial strains have been designed to upgrade pCA into resveratrol, an antioxidant with potential benefits for human health [64][65][66], as well as the biofuel precursor bisabolene [18], the platform chemical muconic acid [67], the biodegradable polyester precursor lactic acid [68], and polyhydroxyalkanoate polyesters [20,69,70]. Moreover, pCA can be transformed chemically to deep eutectic solvents potentially useful for biomass pretreatments [40] and converted to different types of high-performance polymers [71,72].…”
Section: P-coumaratementioning
confidence: 99%